Determination of earthquake prone zones at university of tadulako based on dominant periods and peak ground acceleration (PGA). Issue 1 (January 2022) - Meidji, I U; Mulyati, S; Janat, N R; Jayadi, H; Asrafil
Abstract: University of Tadulako is the largest State University in Palu City. When an earthquake with a magnitude of 7.4 Mw on September 28, 2018, occurred, many buildings were damaged and even collapsed at that time, even causing casualties due to the rubble. Research on the Local Site Effect is essential for the assessment of seismic hazard. In this study, the local site effect was analyzed using the HVSR method based on microtremor data. The predominant Period (To) ranges between 1.709 s to 3.816 s, indicates that this area consists of alluvium and has a very thick sediment layer. Another parameter calculated in this paper is the peak ground acceleration (PGA) with values from 0.914 g to 0.924 g. This value is the first indicated soil damage level due to ground motions. The results of this study can be used as a consideration in the development of regional spatial planning and building structures based on earthquake analysis.